(untitled) (Comprehensive Journal of Science, 2026)
This study explores the presence and influence of prototype effects among English language learners in secondary schools in Ajelat City, Libya. Prototype effects, a central concept in cognitive linguistics, refer to how learners categorize words or concepts around typical or ’best example’ members within a category. The study aims to identify how prototype theory manifests in learners’ understanding of English vocabulary, particularly in semantic categorization tasks. A small-scale empirical study was conducted involving 60 secondary school students from three schools in Ajelat. Data were collected through categorization tests, vocabulary association tasks, and semi-structured interviews. Findings indicate that most students demonstrate strong prototype-based categorization patterns, favoring central members (e.g., ’sparrow’ for the category ’bird’) over peripheral ones (e.g., ’penguin’). The results provide insight into how cognitive categorization influences English vocabulary learning and suggest pedagogical strategies for vocabulary teaching grounded in cognitive linguistic theory.